Plasmacytoid Urothelial Carcinoma of the Bladder Metastatic to the Stomach: A Case Report - Philippe Nabbout; James Furr; Murugan Paari; Gennady Slobodov (Case Reports in Urology)
Introduction. Plasmacytoid urothelial carcinoma (PUC) of the bladder is a rare histological variant of urothelial carcinoma that was recently identified. Available data on this histological variant is limited. Case Report. We report the case of a 75-year-old man with presumed history of high-grade urothelial cancer of the bladder, treated with transurethral resection and Bacille Calmette-Guérin (BCG) in 2004. Six years after treatment of the bladder cancer, the patient underwent gastrectomy for an undifferentiated carcinoma of the stomach. On followup, patient developed right ureterohydronephrosis and peritoneal carcinomatosis. Biopsy of the bladder during stent placement revealed a plasmacytoid urothelial carcinoma of the bladder. Rereadings revealed that the initial bladder and gastric malignancies were also plasmacytoid carcinoma, indicating that, the patient had since 2004, a PUC of the bladder that spread to the stomach and peritoneal cavity. Conclusion. Plasmacytoid urothelial carcinoma of the bladder is an aggressive variant of urothelial carcinoma. Based on our case and the literature review, this tumor can be misdiagnosed because of its rarity, leading to treatment delays. Both the urologist and the pathologist need to have a high index of suspicion for PUC whenever they encounter unusual clinical and/or pathological findings.